Overview of Supporting Factors Affecting Behavior in Pap Smear Examination in Women of Childbearing Age to Prevent Cervical Cancer in Merakurak Health Center - mariyatul qiftiyah (Jurnal Penelitian, 2019)
The coverage of pap smears in the area of the community health center was comprised of 10 villages in 2017, the number of women of reproductive age was 9150 people and the women who followed the pap smear were 50 people (0.5%) while from the data in the community health center merakurak should target set which follows the Pap Smear of 92 people (1%). Various factors that cause women of childbearing age do not do Pap Smear include knowledge, attitude, education, age, occupation and status marriage. This study aims to determine the description of supporting factors that influence the behavior in the Pap smear examination in women of childbearing age to prevent cervical cancer in the Merakurak community health center.This research is a descriptive research. The population is some women of childbearing age who follow Pap Smear at Merakurak Public Health Center in 2017. The sampling technique using purposive sampling with the number of samples of 25 women of childbearing age.How to collect data using questionnaires. The variables in this study are the influence of knowledge, attitude, education, age, occupation, marital status of women of childbearing age in early detection of cervical cancer with Pap Smear method.Result of research from 25 respondents, it is found that most of respondent 52% have knowledge of less, 72% have negative attitude and 56% woman of childbearing age who follow pap smear 20 years old and 35 years old. Half are educated moderate 44% and all respondents who follow the pap smear status get 100% married.The conclusion of this study that there are still many women of childbearing age who do not do Pap Smear. so that the role of midwives to increase knowledge and change the attitude of women of childbearing age such as giving counseling about the importance of Pap smear examination to prevent cervical cancer, so women of childbearing age want to do Pap Smear